Face of war : New Zealand's great war photography - Callister, Sandy (Auckland University Press, 2008)
An authoritative history of combat photography and its cultural, emotional, and memorial roles, this collection is the first to examine the vernacular photos of World War I taken by its New Zealand participants. The book discusses how photography was used to capture and narrate, memorialize and observe, romanticize and bear witness to the experiences of New Zealanders at home and abroad. The first to argue for the importance of New Zealand photography to the history of war, this overview examines in depth the contradictions of war photography, as a site of.